The association of osteopenia with levels of serum 25-hydroxyvitamin D and HOMA-IR values - YOLDEMİR, AHMET TEVFİK; YAVUZ, DİLEK (TAYLOR & FRANCIS LTD, 2014)
Objective To determine the association of osteopenia with levels of serum 25-hydroxyvitamin D and HOMA-IR values in postmenopausal women. Methods One hundred healthy postmenopausal women were included in a cross-sectional study. Venous blood was collected after an overnight fast and 25-hydroxyvitamin D, glucose and insulin levels were measured. HOMA-IR was calculated. Bone mineral density was measured with a dual X-ray absorptiometer. Results There was no difference in serum 25-hydroxyvitamin D levels and HOMA-IR values between the two groups. A weak positive correlation between serum 25-hydroxyvitamin D levels and osteopenia was detected. Insulin resistance had a weak negative association with osteopenia. Conclusions The correlations between osteopenia and serum 25-hydroxyvitamin D levels and HOMA-IR values were weak among early postmenopausal women.
Keywords: POSTMENOPAUSE; 25-HYDROXYVITAMIN D; HOMA-IR; INSULIN RESISTANCE; VITAMIN-D SUPPLEMENTATION; IMPAIRED GLUCOSE-TOLERANCE; BONE-MINERAL DENSITY; D DEFICIENCY; INSULIN-SECRETION; HYPOVITAMINOSIS-D; WOMEN; FRACTURE; CALCIUM; RISK